Classificasion of Graduate Data Using The C4.5 Algorithm - Ratna Oktavia; Agus Sifaunajah (LPPM Universitas KH. A. Wahab Hasbullah, 2022)
Data mining is an activity that includes the collection, and use of historical data to find regularities, patterns, or relationships in large data sets. The pile of data in an information system gives rise to a data mining process. The Bahrul Ulum Islamic Boarding School Tambakberas Jombang is one of the oldest and largest Islamic boarding schools in East Java, with a large number of students each year. A large number of graduates in Islamic boarding schools requires the application of data mining processes. The c4.5 algorithm is one of the data mining algorithms that can be used to classify. The classification method is used to determine whether graduates are successful or not, with the parameter that becomes the root of the calculation results, namely work. The evaluation results show that the C4.5 algorithm has an accuracy rate of 84.00%, classification recall gets 93.33%, classification precision gets 85.00%, and an AUC score of 0.850.